Purple Staining of Archaeological Human Bone: An Investigation of Probable Cause and Implications for Other Tissues and Artifacts. (31st May 2016) - Cole, Garrard; Waldron, Tony
Abstract : Excavations in the 1990s at the medieval Chapter House of Worcester Cathedral, UK, revealed medieval human skeletal remains, some of which exhibited a distinctive purple coloration. The nature of the colored bone was investigated using solvents for stain extraction, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), X-ray fluorescence (XRF), plane polarized (PPL) and cross-polarized (XPL) light microscopy, and auto fluorescence (AF) microscopy. Normal bone from the cemetery was used as a control. The color does not arise from a stain soluble in normal organic solvents. EDX and XRD analysis showed no significant difference between purple and normal bone. XRF analysis shows the presence of trace levels of iron, manganese, zinc, and copper in the affected material. This exhibited a pink color in acid phase and a blue color in alkaline phase. These two states were reversible. The alkaline phase gradually changed irreversibly to yellow over time. These data suggest that the coloration is consistent with the presence of high levels of purple acid phosphatase (PAP) enzyme. The presence of trace amounts of iron, manganese, zinc, and copper suggests a plant or fungal origin for the putative PAP, possibly a member of the Aspergillus ficuum species.